Obesity awareness among Malaysian - Othman, Noratikah (IIUM Press, International Islamic University Malaysia, 2017)
Overweight and obesity is growing to become one the world’s most major concern. Once thought to be a problem exclusive to high-income countries, overweight and obesity is now on the rise even in low and middle-income countries especially in the metropolitan setting. This shows the growing concern that overweight and obesity has on the population of children worldwide and its correlation to depression. At the same time, it is also important to tackle the obesity problem among schizophrenic patient as depression is one of early warning signs of schizophrenia. It is essential to understanding consumer perceptions and knowledge of public awareness about obesity to design an effective multimedia and public relations campaign supporting obesity prevention.